(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Interactive learning media are crucial for enhancing elementary education, yet many teachers rely on conventional methods that fail to engage students. Specific Background: Canva, a user-friendly graphic design platform, offers potential for creating effective media, but teachers lack training to utilize it. Knowledge Gap: There is limited focus on integrating technical skills with pedagogical principles in teacher training. Aims: This study aimed to improve teacher competence in creating interactive learning media through Canva training. Results: Training with 24 teachers from SD Muhammadiyah Krian showed an 85% increase in competence, improved creativity, and confidence in using technology. Novelty: The program integrated instructional design principles, combining technical and pedagogical skills. Implications: Practical, technology-based training like this can advance educational quality and support digital transformation in teaching practices. Highlights: • Canva empowers teachers to create engaging and effective interactive learning media. • Training combines technical skills with pedagogical principles for holistic improvement. • Results show significant competence gains, boosting creativity and teaching confidence. Keywords: Canva, Teacher Training, Interactive Media, Digital Education, Elementary Schools